Influence of Pb Dosage on Immobilization Characteristics of Different Types of Alkali-Activated Mixtures and Mortars - Jan Koplík; Jaromír Pořízka; Lukáš Kalina; Jiří Másilko; Matěj Březina (Advances in Materials Science and Engineering)
Alkali-activated matrices are suitable materials for the immobilization of hazardous materials such as heavy metals. This paper is focused on the comparison of immobilization characteristics of various inorganic composite materials based on blast furnace slag and on the influence of various dosages of the heavy metal Pb on the mechanical properties and fixation ability of prepared matrices. Blast furnace slag (BFS), fly ash, and standard sand were used as raw materials, and sodium water glass was used as an alkaline activator. Pb(NO3)2 served as a source of heavy metal and was added in various dosages in solid state or as aqueous solution. The immobilization characteristics were determined by leaching tests, and the content of Pb in the eluate was measured by inductively coupled plasma optical emission spectroscopy (ICP-OES). The microstructure of matrices and distribution of Pb within the matrix were determined by scanning electron microscopy (SEM) equipped with energy dispersive X-ray spectroscopy (EDS). Increasing the dosage of the heavy metal had negative impacts on the mechanical properties of prepared matrices. The leaching tests confirmed the ability of alkali-activated materials to immobilize heavy metals. With increasing addition of Pb, its content in eluates increased.